Full-Length Transcriptional Analysis of the Same Soybean Genotype With Compatible and Incompatible Reactions to Heterodera glycines Reveals Nematode Infection Activating Plant Defense Response - Huang, Minghui; Jiang, Ye; Qin, Ruifeng; Jiang, Dan; Chang, Doudou; Tian, Zhongyan; Li, Chunjie; Wang, Congli (Frontiers in Plant Science, 2022)
Full-length transcriptome sequencing with long reads is a powerful tool to analyze transcriptional and post-transcriptional events, yet it has not been applied on soybean (Glycine max). Here, a comparative full-length transcriptome analysis was performed on soybean genotype 09-138 infected with soybean cyst nematode (SCN, Heterodera glycines) race 4 (SCN4, incompatible reaction) and race 5 (SCN5, compatible reaction) using Oxford Nanopore technology. Each of 9 full-length samples collected at 8 days post inoculation with/without nematodes generated an average of 6.1 GB clean data and a total of 65,038 transcript sequences. After the redundant transcripts were removed, 1,117 novel genes and 41,096 novel transcripts were identified. By analyzing the sequence structure of the novel transcripts, a total of 28,759 complete ORF (open reading frame) sequences, 5,337 transcription factors, 288 long noncoding RNAs, and 40,090 novel transcripts with function annotation were predicted. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis of differentially expressed genes (DEGs) revealed growth hormone, auxin-activated signaling pathway and multidimensional cell growth and phenylpropanoid biosynthesis pathway were top enriched by infection with both nematode races. More DEGs associated with stress response elements, plant-hormone signaling transduction pathway and plant-pathogen interaction pathway with more upregulation were found in the incompatible reaction with SCN4 infection, and more DEGs with more downregulation involving in cell wall modification and carbohydrate bioprocess were detected in the compatible reaction with SCN5 infection when compared with each other; among them, overlapping DEGs with quantitative difference were triggered. The combination of protein-protein interaction with DEGs for the first time indicated that nematode infection activated the interactions between transcription factor WRKY and VQ (valine-glutamine motif) to contribute to soybean defense. The knowledge of SCN-soybean interaction mechanism as a model will present more understanding for other plant-nematode interactions.